Trabalho de inovação financeira em fintechs: percepção dos trabalhadores em uma startup de São Paulo - Momente, Luísa de Carvalho (Universidade Federal de São Carlos, 2021)
With the technological revolution at the end of the 20th century, behavioral changes occurred in contemporary society, which also impacted labor relations in companies. The objective was to assess the perception of workers at a fintech about pleasure and suffering at work, in addition to comparing the work environment of a startup and traditional companies. To achieve this goal, interviews were conducted with 10 employees from the administrative, commercial and financial areas of a fintech located in the city of São Paulo, Brazil. From the responses collected, it was possible to understand the perception of these workers and identify the conditions of the work environment, the requirements, results, cooperation and competitiveness present in this environment. According to the results, fintechs present an environment without hierarchies, flexible, which promotes creativity and reasoning, these elements directly influence the mental activity and pleasure of employees during their work. Some experiences that generate suffering were also identified, such as competitiveness, doubt about the ability to perform tasks and stress. It is concluded that it is extremely important to seek balance in this work environment based on the perception of those who perform it, enhancing the experiences that generate pleasure and restricting those that generate suffering.
Finance innovation work in fintechs: workers perception from a startup in São Paulo city
Keywords: Inovação financeira; Fintechs; Startup; Psicodinâmica do trabalho; Finance innovation; Psychodynamics of work; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS